Heterogeneity in the in vitro susceptibility of Loa loa microfilariae to drugs commonly used in parasitological infections - Abdel J. Njouendou; Fanny F. Fombad; Maeghan O’Neill; Denis Zofou; Chuck Nutting; Patrick C. Ndongmo; Arnaud J. Kengne-Ouafo; Timothy G. Geary; Charles D. Mackenzie; Samuel Wanji (Parasites & Vectors, 2018)
Abstract Background Co-infection with loiasis remains a potential problem in control programs targeting filarial infections. The effects of many anti-parasitic drugs often administered to Loa loa infected people are not well documented. This study compared the in vitro activity of several of these drugs on the viability of L. loa microfilariae (mf). Methods Human strain L. loa mf were isolated from baboon blood using iso-osmotic Percoll gradient, and cultured in RPMI 1640/10% FBS with antimalarial drugs (mefloquine, amodiaquine, artesunate, chloroquine and quinine), anthelmintics (ivermectin, praziquantel, flubendazole and its reduced and hydrolyzed metabolites), two potential trypanocidal agents (fexinidazole and Scynexis-7158) and the anticancer drug imatinib. The drug concentrations used varied between 0.156 μg/ml and 10 μg/ml. Mf motility (CR50 = 50% immotility) and a metabolic viability assay (MTT) were used to assess the effects of these drugs on the parasites. Results Mf in control cultures showed only a slight reduction in motility after 5 days of culture. Active inhibition of Loa loa motility was seen with mefloquine and amodiaquine (CR50 values of 3.87 and 4.05 μg/ml, respectively), immobilizing > 90% mf within the first 24 hours: mefloquine killed the mf after 24 hours of culture at concentrations ≥ 5 μg/ml. SCYX-7158 also induced a concentration-dependent reduction in mf motility, with > 50% reduction in mf motility seen after 5 days at 10 μg/ml. The anticancer drug imatinib reduced mf motility at 10 μg/ml from the first day of incubation to 55% by day 5, and the reduction in motility was concentration-dependent. Praziquantel and fexinidazole were inactive, and FLBZ and its metabolites, as well as ivermectin at concentrations > 5 μg/ml, had very minimal effects on mf motility over the first 4 days of culture. Conclusions The considerable action of the anti-malarial drugs mefloquine and amodiaquine on Loa mf in vitro highlights the possibility of repurposing the existing anti-infectious agents for the development of drugs against loiasis. The heterogeneity in the activity of anti-parasitic agents on Loa loa mf supports the need for further investigation using animal models of loiasis.